«Velvet» Revolutions as Political Technologies: Foreign Experience - Ekaterina Gennadievna Ilyinova (Проблемы постсоветского пространства, 2017)
This article analyzes the geopolitical struggle by means of “revolutions” as the instrument for organizing the coup d’etat. Using the extensive sources, the author studies the causes, driving forces, the role of external factors in preparation and accomplishment of coup d’etat.